Consumer Potential of the East Asian Region: Contemporary Trends and Opportunities for Russia - E. Y. Arapova (Международная аналитика, 2019)
The article aims at assessing consumer potential of the East Asian region in the context of diversification of economic growth sources and its transition to consumption-led economic growth model. Favorable social, demographic and economic trends, as well as demand-stimulating policies, implemented by governments and monetary authorities of the most of regional economies, entail a rapid increase in the private consumption contribution to economic growth, lead to a gradual transformation of the commodity structure of consumption, and import demand, which opens up new opportunities for exporters from the third countries, including Russia. The analysis made it possible to make a number of practical conclusions. Given consumer potential and mutual trade dynamics, China and Vietnam, to a lesser extent Malaysia, are of the greatest interest to Russia, while Thailand, Indonesia and the Philippines’ potential can be implemented in medium-term perspective (5-10 years). Russian mining, agricultural and heavy engineering industries (mainly, aircraft, space and power engineering) can become the key beneficiaries of the growing consumer potential in East Asia.